Ejecución presupuestaria del Consejo Nacional Electoral Delegación Los Ríos y el registro en el sistema de pagos Esigef en el periodo 2023. - Luque Muñoz, Selena Camila (2024)
The investigation of this Thesis is based on the budget that the government gives to public institutions and the problem of this investigation arises from the lack of payments to the personnel who worked with an invoice in the electoral process, since due to lack of funds the Ministry does not proceeded to make the pending payments. And due to a bad procedure through the ESIGEF page, the corresponding payment to the Administrative and electoral staff was not made. Since the main objective is to analyze the budget and payment matrices.